Estudo de Redes Ad-Hoc sem fio pela abordagem de geometria estocástica - Guimarães, Antonio Alisson Pessoa (2014)
Currently, cellular technology is present in all aspects of everyday life: homes, offices, industries, etc. Such technology had grown rapidly over the last two decades trying to follow up with the increased traffic volume on the networks of wireless communication. Naturally, to propose possible more realistic models, with the purpose of characterizing phenomena that affect the signal quality or performance system, new ideas, concepts and other tools to describe such situations arise. This is the case of Stochastic Geometry or, particularly, the point process Poisson, which has been often used as a model for cellular network from the random node locations in the network. Faced with this mathematical tool, it is possible deploy base stations in cellular external network and access points based picocells, femtocells, etc. Moreover, it allows to quantify the interference, coverage area, outage probability, among others. These results also consider the impact of mobility on the performance of such networks. In this context, this thesis will analyze ad-hoc wireless networks offering analytical expressions for the following metrics of performance characterization: interference and transmission connections. These metrics take into account both signal-to-interference-plus-noise ratio (SINR) and signal-to-interference ratio (SIR), in which case, the noise power is considered null. Specifically, the interference phenomena will be characterized via shot-noise model according to a point process called marked point process (MPP), this being more realistic than the traditional Poisson model. Furthermore, this type of model incorporates effects of radio propagation small and large scale, mainly the different technologies for the detection and signal processing. In parallel, we will adopt a radio channel with Nakagami-m fading. Finally, the mathematical treatment for the proposed model becomes a challenging factor in this work, since such results generalize some already published in the literature, which adopt some less realistic parameters